Niveles del lenguaje oral en niños de cuatro años en instituciones educativas de la Red N° 5, distrito Callao - Caycho Torres, Ana Isabel (2010)
The purpose of this research is to know the level of the 4 years old students' oral language in educational institutions of the Red District No. 5 in Callao. The descriptive research is simple. Participants were 94 girls and 95 boys randomly selected. We administered the Oral Language Test of Navarra - Revised and adapted to our reality for purposes of the investigation. The results showed that 63.0% of students achieved the normal level, while 13.2% achieved a delay level and 23.8% of the students were in intermediate level and. In the results, there were not significant differences between the level of language and gender ofstudents. In conclusion, the majority of students are placed at the normal level of oral language.